2018
DOI: 10.1016/j.neuron.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Tau in Alzheimer’s Disease

Abstract: The microtubule-associated protein tau and amyloid-β (Aβ) are key players in Alzheimer's disease (AD). Aβ and tau are linked in a molecular pathway at the post-synapse with tau-dependent synaptic dysfunction being a major pathomechanism in AD. Recent work on site-specific modification of dendritic and more specifically post-synaptic tau has revealed new endogenous functions of tau that limits synaptic Aβ toxicity. Thus, molecular studies opened a new perspective on tau, placing it at the center of neurotoxic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
210
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(216 citation statements)
references
References 179 publications
(267 reference statements)
4
210
0
2
Order By: Relevance
“…This work highlights the potential of AAVs to test several variants of a protein in a time sensitive manner in vivo. Conceptually, this work challenged the long-standing idea of Tau phosphorylation being a purely disease-driven event (Ittner & Ittner, 2018) and suggested that further work is required to examine the physiological and pathological relevance of phosphorylation of Tau protein at individual sites. AAVs offer the opportunity to perform testing of larger number of Tau variants in relevant neuronal culture and in vivo (i.e., disease) models.…”
Section: Post-synaptic Tau Protein In Admentioning
confidence: 95%
“…This work highlights the potential of AAVs to test several variants of a protein in a time sensitive manner in vivo. Conceptually, this work challenged the long-standing idea of Tau phosphorylation being a purely disease-driven event (Ittner & Ittner, 2018) and suggested that further work is required to examine the physiological and pathological relevance of phosphorylation of Tau protein at individual sites. AAVs offer the opportunity to perform testing of larger number of Tau variants in relevant neuronal culture and in vivo (i.e., disease) models.…”
Section: Post-synaptic Tau Protein In Admentioning
confidence: 95%
“…Tau is a predominantly cytoplasmic protein that localizes to axons in mature neurons, where it stabilizes the microtubule cytoskeleton. However, Tau mislocalizes to soma and dendrites in tauopathy (Ittner & Ittner, 2018). Furthermore, nuclear or perinuclear localization of Tau has been described (Frost, Hemberg et al, 2014, Maina, Bailey et al, 2018, Sotiropoulos, Galas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These dissociated forms of tau can self-assemble into paired-helical filaments (PHFs) gaining further potential to aggregate as Neurofibrillary tangles (NFTs) -a classical neuropathological hallmark of Alzheimer's disease (AD) and related tauopathies 9 . Alternatively, hyperphosphorylated and pathological tau (p-Tau) has been shown to acquire gain-of-toxic function in triggering synaptotoxicity relevant to AD 10 . While AD is the most common form of tauopathy and sixth leading cause of death in the United States 11 , NFT pathology is also the primary etiology in many, but rare tauopathies such as Progressive Supranuclear Palsy (PSP), Pick's disease (PiD), Corticobasal Degeneration (CBD), Fronto-temporal Dementia and Parkinsonism linked to Chromosome-17 tau-type (FTDP-17T) and others 12 .…”
Section: Introductionmentioning
confidence: 99%